"Another Munich We Just Cannot Afford": Historical Metonymy In Politics. (1st September 2016) - Nyyssönen, Heino; Humphreys, Brendan
Abstract : The appeasement of Hitler and the Munich Agreement is a rhetorical comparison used commonly in international relations to defend politico-military action. On the basis of conceptual history and rhetorics, we examine cases of political speech in this paradigm. Firstly, we discuss time and conceptualize experience into first and second order experiences. Secondly, the roles of metaphor, metonymy and analogy in relation to thought and action are examined. We then contextualise Munich 1938, and present three cases demonstrating the political usage of this metonymy since WWII. These range from the Suez Crises to the Gulf War and on-going War on Terror. These cases show that "Munich" can be used in multiple contexts. Our hypothesis is that "Munich" has proved very instrumental politically; it has been a key element in the final push to use force on numerous occasions, and we conclude that it is a very dangerous form of anti-diplomacy.